“Estudio del comportamiento postcosecha de cuatro variedades de piña (Ananás comosus) bajo dos sistemas de almacenamiento” - Mas Golac, Werther Exequiel (2006)
Presently work was studied the behavior post-crop of four pineapple varieties with the purpose of predicting the low time of conservation the systems of refrigerated storage (10±2ºC) and ambient temperature (28 ±2ºC). The work was developed in the Plant Pilot of Fruits and Vegetables of the Ability of Agroindustrial Engineering of the National University of San Martín -Tarapoto. The mensurations and the determination of results were carried out each, 2 days until the ninth day, of there from now on every four days, that which allowed us to select the good time of duration of the low fruit the two storage systems; being used a Complete Design at random with factorial arrangement of 4x3x2 (Varieties * states of maturity *temperaturas), with a total of 24 treatments, being analyzed the results, by means of the variance analysis (ANVA); continued by the test of DUNCAN with a level of 5% of probability, for the analysis of the difference among the stockings. The four pineapple varieties (Cayena Lisa, Nativa Lamas, Perolera and Red Trujillana) with three states of commercial maturity, they were gathered of a property located in the sector High May, Brown District Miguel County from Rioja. They were carried out operations like; it harvests, selection, laundry, immersion in wax liquidates, packed and stored; later on the parameters of quality were evaluated: loss of fresh weight, color of the shell, color of the pulp, resistance of the pulp to the pressure, total soluble solids, acidity titulable, index of maturity, pH. They were also evaluated the acceptability in the four pineapple varieties. The two storage temperatures in the four pineapple varieties didn't show significant effect on the acidity titulable, the pH and pulp color; on the contrary the two storage temperaturas determinad variations in the behavior of the variable loss of fresh weight, shell color, resistance of the pulp to the pressure, total soluble solids and index of maturity. The pineapple fruits stored to refrigeration temperatura 1 O ±2ºC slowed sorne relative changas to the maturation process in two weeks with regard to the fruits stored to ambient . temperature 28 ±2ºC, lengthening in consequence their period of commercialization. The state of maturity presentad accented effect on the time of useful life of the pineapple fruits stored to refrigeration temperature 10±2°C and to the environment 28 ± 2ºC, being the fruits gathered in state green lemon those that had bigger useful life. In conclusion of the four varieties, studied the variety "Nativa Lamas" it is for direct and immediate consumption to exhibit characteristic that make it highly palatable. The Varieties "Cayena Lisa" and "Perolera" it is recommended for industrial use due to their medium concentration of sugar and size; while the variety "Red Trujillana" for their size, high resistance to the pressure and poverty in sugars, is recommended as forage.